1991
DOI: 10.1016/0735-1097(91)90586-x
|View full text |Cite
|
Sign up to set email alerts
|

Proarrhythmia, cardiac arrest and death in young patients receiving encainide and flecainide

Abstract: The potential for proarrhythmic responses to the class IC sodium channel-blocking drugs encainide and flecainide has not been well described in young patients. Therefore, data were retrospectively collected from 36 institutions regarding 579 young patients who were administered encainide or flecainide for treatment of supraventricular tachycardias (encainide 86 patients, flecainide 369 patients) or ventricular arrhythmias (encainide 21 patients, flecainide 103 patients) to assess the frequency of proarrhythmia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
7

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(61 citation statements)
references
References 35 publications
2
52
0
7
Order By: Relevance
“…Ablation of the accessory pathway(s) in high-risk patients was also examined in 1 RCT that enrolled 76 patients, showing that arrhythmic events (defined as symptomatic SVT, AF, and ventricular fibrillation in this study) occurred in 7% of patients who underwent ablation versus 77% who did not undergo ablation. 302 Another study that examined patients on the basis of whether an ablation was performed reported that none of the asymptomatic patients who had undergone ablation of the accessory pathway developed a malignant arrhythmia during 8 years of follow-up. The risk of complications with ablation ranged from 0.1% (complete heart block) to 0.9% (ablation-induced right bundle-branch block).…”
Section: IIImentioning
confidence: 99%
“…Ablation of the accessory pathway(s) in high-risk patients was also examined in 1 RCT that enrolled 76 patients, showing that arrhythmic events (defined as symptomatic SVT, AF, and ventricular fibrillation in this study) occurred in 7% of patients who underwent ablation versus 77% who did not undergo ablation. 302 Another study that examined patients on the basis of whether an ablation was performed reported that none of the asymptomatic patients who had undergone ablation of the accessory pathway developed a malignant arrhythmia during 8 years of follow-up. The risk of complications with ablation ranged from 0.1% (complete heart block) to 0.9% (ablation-induced right bundle-branch block).…”
Section: IIImentioning
confidence: 99%
“…Conversely, isolated ventricular ectopy is common in older postoperative congenital heart disease patients. In the absence of ventricular dysfunction or symptoms, isolated ventricular ectopy has minimal prognostic significance, and the risks of antiarrhythmic drug treatment can exceed any potential benefit (431). There remain many patients with simple or complex ventricular ectopy, with vague symptoms, or modest impairment of ventricular function who require individual judgment regarding the need for evaluation and treatment (432).…”
Section: Recommendationsmentioning
confidence: 99%
“…In addition, treatment with antiarrhythmic medications may have limited efficacy and higher incidence of side effects than in patients with structurally normal hearts. 10,11 Therefore, AVNRT Ablation in Congenital Heart Disease it is important to recognize the patterns of relationship of AVNRT with CHD and any difficulties in its transcatheter management and outcome. There have been previous case reports or case series on patients with specific forms of CHD, and, as well, a recent single-center retrospective study on this subject has been published.…”
mentioning
confidence: 99%